Retinal oximetry images must be standardized: a methodological analysis. - Palsson, Olafur; Geirsdottir, Asbjorg; Hardarson, Sveinn Hakon; Olafsdottir, Olof Birna; Kristjansdottir, Jona Valgerdur; Stefánsson, Einar (Investigative Opthalmology & Visual Science, 2013)
To access publisher's full text version of this article. Please click on the hyperlink in Additional Links field. Retinal vessel oximetry is a new technology and needs detailed methodological scrutiny. We determine (1) the repeatability of retinal vessel oxygen saturation measurements, (2) whether measured saturation is different between retinal quadrants, and (3) whether the angle of gaze changes measurements of the same vessels. Fundus oximetry images were obtained from 26 healthy individuals, 18 to 30 years old, using the Oxymap retinal oximeter. Oxygen saturation in the same vessel segments was compared between two similar images of each individual to determine repeatability. Vessel oxygen saturation was also compared between different quadrants of the retina in the same oximetry image. Finally, oxygen saturation measurements were made on the same vessel segments at different angles of gaze. Mean and standard deviation of saturation measurements was 93.1% ± 2.3% in arterioles and 64.9% ± 3.3% in venules. Standard deviation of repeated saturation measurements on the same vessel segment was 1.0% in arterioles and 1.4% in venules. Significant differences were seen between retinal quadrants. When angle of gaze was altered, measured saturation was lower in the same vessels when they were located in the inferior portion compared with other parts of the image (-1.3% ± 1.7%, P = 0.0004 in arterioles and -1.9 ± 2.4%, P = 0.0007 in venules). Retinal vessel oxygen saturation measurements are repeatable with a small standard deviation. When oximetry results are compared between time points or eyes, the imaging must be standardized and similar parts of the images analyzed. Icelandic Center for Research (Rannis) University of Iceland Research Fund Landspitali University Hospital